1993
DOI: 10.1080/07391102.1993.10508717
|View full text |Cite
|
Sign up to set email alerts
|

Raman and Infrared Studies of Wet-Spun Films of Na-Hyaluronate

Abstract: Raman and infrared (IR) studies of Na-hyaluronate films have been performed as a function of relative humidity (RH) and temperature. These data show a number of vibrational modes. Certain of these modes are evident in both the Raman and IR data. Changes in the Raman spectra are observed at the order-disorder phase transition (between 84 and 90% RH) and suggest that the molecular conformation changes at the phase transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In previous 13 C-NMR studies of HA in the solid state, we found evidence for significant conformational differences relative to HA in aqueous solution ,…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…In previous 13 C-NMR studies of HA in the solid state, we found evidence for significant conformational differences relative to HA in aqueous solution ,…”
mentioning
confidence: 55%
“…19 Additional evidence for a change in HA conformation upon hydration has been obtained by Brillouin and X-ray scattering, as well as Raman and infrared spectroscopy. 20,21 The conformation adopted by HA in aqueous solution is the subject of continuing study. HA is a polyanion and exhibits typical polyelectrolyte properties in response to changes in its ionic environment.…”
mentioning
confidence: 99%
“…The first IR and Raman spectra of GAGs were published more than 50 and 30 years ago,7, 8 respectively. Later studies analyzed the differences of the spectra in solid‐state and in aqueous solutions,9 or with different hydration rates10–15 or from different species (CS from different sources of cartilage, such as crocodile, shark, chicken, ray) 16. Several peaks were identified by spectral comparison,17 especially those associated with sulfate vibrations8, 18–21 and different conformations of iduronate 22–25.…”
Section: Introductionmentioning
confidence: 99%
“…Even at fairly low concentration, it forms highly viscous aqueous solutions. The conformation of the HA chains has been studied for some time using a couple of methods including NMR, , Raman, and infrared spectroscopy, electron microscopy, , neutron and X-ray scattering, vacuum ultraviolet circular dichroism, and computer simulation …”
Section: Introductionmentioning
confidence: 99%